MEMBEDAH PEMIKIRAN HASAN AL-BANNA TENTANG NASIONALISME - Muchtarom, Moh. (PKn Progresif, 2008)
Islam is a guide for living that Moslems used not only as a religion–studies in the West, but it is also system that covers all aspects of human life. The universality of Islam as a religion and social system can be evidenced from the four aspects: metaphysical, religious, sociological and political aspect. As the faith of the monotheism of God in which is applied in very strong believe, Islam is a universal ideology that can not be equated with other ideology and religion. In relation with politics, Islam provides strong foundation. Nationalism is a small part of the political system of Islam. One figure who has harmonized between Islam and nationalism is Hasan Al-Banna, a charismatic contemporary scholar of Egypt. Through the establishment of Moslem Brotherhood, Al-Banna becomes most important figure in the Islamic world a successful merge between thought and movement in a return Muslims to their believe.